Picosecond time-resolved photoluminescence at detection wavelengths greater than 1500 nm. - Smith, J; Hiskett, P; Buller, G (2001)
We report what is to our knowledge the first application of high-efficiency InGaAs/InP photon-counting diode detectors in time-resolved photoluminescence measurements at wavelength greater than 1500 nm. When they were cooled to 77 K and used in conjunction with the time-correlated single-photon counting technique, the detectors were capable of an instrumental response of 230 ps and a noise equivalent power of 2x10(-17)W Hz(-1/2) . Preliminary measurement of a semiconductor heterostructure indicates sensitivity at photogenerated carrier densities as low as 10(14)cm (-3) . This development facilitates the detailed characterization of dominant recombination mechanisms in semiconductor optoelectronic materials and devices designed to operate in the third telecommunications spectral window.